The Validity and Practicality of Augmented Reality-Based Media Development on Science Matter - Siahaan, Sardianto Markos; Patriot, Evelina Astra; Scristia, Scristia; Helen, Helen; Kalsum, Umi; Putri, Regita Elsa (FKIP Universitas Lampung, 2023)
Abstract: Augmented reality is a learning media developed massively and utilized by educators to visualize abstract science concepts into concrete concepts. This study aims to analyze the validity and practicality of augmented reality-based media development on science matter to enhance science conceptual learning. This research is development research conducted to design products of learning media based augmented reality. The development model used is the Alessi and Trollip development model, which concentrates on augmented reality media development. The stage in this research, namely, planning stage, design stage and development stage. The data analysis technique used a questionnaire instrument and the technical descriptive statistical analysis. The results of this study are: the development of augmented reality-based learning media on water cycle and earth rotation material in the form of consisting of competencies and indicators, picture, sound, materials, and mini test; validity assessment by material experts with an average score of 94.44% in the